SOFTWARE COMPLEX FOR PARTS RECOGNITION AS THE BASIS OF EDUCATIONAL LABORATORY WORK - Samarkin, Alex; Samarkina, Elena; Belov, Vladimir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article discusses the scientific and methodological foundations of laboratory work in vision systems using the author's algorithms for pattern recognition. The results were used to prepare masters of technical specialties at the Pskov State University. Another approach to using digital technologies for processing images of the working area is proposed. Some aspects of solving problems of identification of parts, determination of their location, control in automated assembly is described. The hardware-software complex in the article performs data processing and measurements in parallel with the flow of the technological process. The hardware and software complex expands the capabilities of flexible assembly platforms when assembling parts with different mass-inertial characteristics due to the geometric shape and dissimilar materials.